Degrading ability of oligocyclic aromates by Phanerochaete sordida selected via screening of white rot fungi - Lee, H; Choi, Y-S; Kim, M-J; Huh, N-Y; Kim, G-H; Lim, Y W; Kang, S-M; Cho, S-T; Kim, J-J (Folia microbiologica, 2010)
Seventy-nine white rot strains were screened to determine if they had the potential for use in the degradation of oligocyclic aromates (PAHs) by measuring their dye-decoloration rate. Fourteen strains that were selected based on their dye-decoloration rate were then evaluated for the ability to tolerate various levels of PAHs spiked in agar medium. The ability of white rot fungi to degrade 3- or 4-ring PAHs (anthracene, phenanthrene, fluoranthene, pyrene) was determined. Two strains of Phanerochaete sordida (KUC8369, KUC8370) were possible PAHs degraders, degrading a significantly greater amount of phenanthrene and fluoranthene than the culture collection strain P. chrysosporium (a known PAHs degrader). The production of manganese peroxidase, the only extracellular ligninolytic enzyme detected during the cultivation, was evaluated.
Keywords: Molecular Sequence Data; Phenanthrenes; DNA, Ribosomal Spacer; Sequence Analysis, DNA; fluoreny; Fluorenes; DNA fungální; Biodegradation, Environmental; biodegradace; Basidiomycota; polycyklické aromatické uhlovodíky; Phanerochaete; fenantreny; peroxidasy; Peroxidases; Polycyclic Aromatic Hydrocarbons; DNA, Fungal; kultivační média; barvicí látky; sekvenční analýza DNA; molekulární sekvence - údaje; Coloring Agents; mezerníky ribozomální DNA; Culture Media